ANALISIS POTENSI USAHA KOPI TERHADAP PENDAPATAN MASYARAKAT KECAMATAN PINOGU KABUPATEN BONE BOLANGO - Machmud, Joice; adam, Herlin (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2024)
This study aims to determine the potential of the coffee business in contributing to community income in Pinogu Subdistrict, Bone Bolango Regency. The research adopts a quantitative approach utilizing both primary and secondary data sources. The instrument used in this study is a questionnaire. The analytical tool employed to address the research problem is the Cost of Ratio (R/C), which compares revenue to total production costs. The findings indicate that the Pinogu coffee business in Pinogu Subdistrict holds significant potential for development as a community economic enterprise. This is evidenced by the income analysis using the R/C or Return Cost Ratio approach, which compares total revenue with the expenses incurred. The analysis results show that the R/C ratio is greater than 1, specifically 7.18 or 7.2. This means that the Pinogu coffee business in Dataran Hijau Village is highly feasible and profitable to pursue. In other words, every rupiah spent can increase income by 72 times. The increase in income from the coffee business can be further enhanced by improving business productivity, as coffee plants in Pinogu Subdistrict thrive, providing an opportunity for the community to boost household income.